The Influence of Service Quality, Perceived Service Quality, Perceived Price Fairness on Customer Loyalty of Gojek Users in Bandung Through Customer Satisfaction and Brand Image a Conceptual Paper - Rafiansyah, Muhammad; Widodo, Arry; Silvianita, Anita; Rubiyanti, Nurafni (PT FORMOSA CENDEKIA GLOBAL, 2025)
The growth of the ride-hailing industry in Indonesia which is estimated to reach US9 billion in 2025 and Indonesia which is the country ranked first in Southeast Asia with the largest market value of online ride hailing and food market makes every service provider must be able to increase and maintain existing customer loyalty, especially Gojek as a ride-hailing service provider from Indonesia. Various previous studies have explored the importance of customer loyalty for a company and how to improve it. Furthermore, the results of the exploration explain that service quality, perceived service quality, perceived price fairness have an effect on customer loyalty with customer satisfaction and brand image mediating it. Based on this, this conceptual paper is expected to be able to provide further and better understanding of things that can influence customer loyalty from the ride-hailing industry.